Visual functioning in adults with Idiopathic Infantile Nystagmus Syndrome (IINS). (2nd October 2018) - Das, Aditi; Quartilho, Ana; Xing, Wen; Bunce, Catey; Rubin, Gary; MacKenzie, Kelly; Adams, Gillian; Dahlmann-Noor, Annegret; Theodorou, Maria
ABSTRACT: Purpose : IINS is associated with mild/moderate visual impairment, strabismus and compensatory head postures (CHP), which can negatively impact quality of life. Standard visual acuity assessments tend to underestimate the effect of IINS on visual functioning. Published evidence on the effect of INS on quality of life is slowly emerging. Our study examines visual functioning of adults with IINS using the National Eye Institute Visual Function Questionairre-25 (VFQ-25). Methods : 38 participants were recruited to participate in the study. All participants underwent detailed clinical examination, as well as appropriate investigations and were asked to complete the self administered VFQ-25. Results : 35/38 participants completed the questionnaire. The mean age of the population was 35.1 years (range 17-64). Mean overall VFQ-25 score at baseline was 65 (SD 13, range 34-91). Participants specifically demonstrated lowest scores for the impact of IINS on mental health, role limitations and dependency. 26/35 of participants were not driving, either due to sub-normal vision, lack of confidence or difficulties with contrast sensitivity. Conclusions : IINS can have a greater than expected impact on an individual's quality of life, without necessarily causing markedly reduced visual acuity. Our study showed lowest scores in the domains of mental health and wellbeing. Patients also reported reduced visual functioning in driving, which can impact adversely on employability and independence. Visual functioning questionnaires such as the VFQ-25 may provide more functional information on the impact of nystagmus on an individual's quality of life than objective measures such as high contrast Snellen and/or LogMAR visual acuity.